Kajian sistematis tentang perspektif perempuan Bali berkasta terhadap pernikahan nyerod: Antara tradisi dan modernisasi - Wagiswari, I Gusti Ayu Suryaning; Valentina, Tience Debora (Jurnal Psikologi Ulayat, 2025)
Nyerod marriage continues to exist within Balinese Hindu society, wherein women from higher castes marry men from lower castes. This study reviews existing literature on nyerod marriage from women's perspectives, exploring the tension between tradition and modernization. The research method used is a literature review, sourced from four databases such as Google Scholar, OpenAlex, Semantic Scholar, and Crossref, with ten articles selected using the PRISMA flowchart. The findings reveal that traditionally, women in nyerod marriages face significant consequences. These include bringing shame upon their families, being required to adopt and constantly display a new social identity at all times, experiencing psychological challenges, shifts in how they communicate with their families, and other forms of social sanction. From a modern perspective, however, nyerod marriage is seen as an act of resistance by high-caste women against traditional norms of partner selection norms, driven more by economic considerations than by a desire to uphold caste hierarchy.